Garantia do casamento às pessoas com Síndrome de Down no Brasil à luz da convenção sobre os direitos das pessoas com deficiência da ONU - Toscano Filho, Antonio Albuquerque (2017)
This applied work study, assessed by a qualitative method and a deductive approach, uses a documental and bibliographical survey and a content analysis to discuss the fundamental right of people with Down Syndrome to constitute a family entity through marriage, having the Cultural Relativism as its instrument of strengthening, in addition to clarifying the social and legal factors that prevent them from performing the affection and happiness through marriage and creation of family entity. The Convention of the Rights of Persons with Disabilities establishes rights inherent in marriage and the formation of a family. Therefore, in view of the need to realize the human rights norms regarding people with Down Syndrome in all aspects related to marriage, family, and socio-affective relationships, on an equal basis with other people, we sought to verify if the Brazilian State Has adopted provisions of domestic law and effective measures of any nature that ensure the exercise of the rights and freedoms contained in the said Convention. History is proof of the long time that the experiences of exclusion mark the life of the social group constituted by people with intellectual disability, who remains in a situation of intense social disadvantage. The central argument of this study is that the assertion of historically defiled rights is not sufficient for its effectiveness. It aims to display the merely formal and abstract vision of the universality of the Human Rights and the lack of respect and disregard by the Brazilian State and other determining reasons for the Convention of the Rights of Persons with Disabilities ineffectiveness, in order to fight discrimination and to promote the full achievement of the exercise of citizenship by people with people with Down Syndrome, so that they can marry and establish family.